Changes in aldolase activity in wild‐type potato plants are important for acclimation to growth irradiance and carbon dioxide concentration, because plastid aldolase exerts control over the ambient rate of photosynthesis across a range of growth conditions - Haake, Volker; Geiger, Michael; Walch‐Liu, Pia; Of Engels, Christ; Zrenner, Rita; Stitt, Mark (The Plant journal : for cell and molecular biology, 1999)
Summary Even though plastid aldolase catalyses a reversible reaction, does not possess properties allowing it to contribute to ‘fine’ regulation, and would therefore be considered unimportant for the control of metabolism and growth, antisense transformants with a 50–70% decrease in aldolase activity showed an inhibition of photosynthesis and growth. We now show that acclimation of photosynthesis to growth conditions includes and requires changes in plastid aldolase activity. Wild‐type potato plants and transformants were grown at low irradiance (70 μmol m–2 sec–1), and at high irradiance (390 μmol m–2 sec–1) at 400 or 800 p.p.m. carbon dioxide. (i) Ambient photosynthesis was always inhibited by a 30–40% decrease of aldolase activity, the strongest inhibition being observed when plants were growing in high irradiance and elevated carbon dioxide. (ii) The inhibition was due to a low rate of ribulose‐1,5‐bisphosphate regeneration in low light, exacerbated by an inadequate rate of starch synthesis in high light and elevated carbon dioxide. Decreased expression of aldolase in antisense transformants was also accompanied by a decrease of fructose‐1,6‐bisphosphatase protein and activity, and Rubisco activity. Transcript levels for the plastid fructose‐1,6‐bisphosphatase and the small subunit of Rubisco did not decrease. (iii) In wild‐type plants, increasing the growth irradiance from 70 to 390 μmol m–2 sec–1 led to a 15–95% increase of the activity of eight Calvin cycle enzymes, and increasing the carbon dioxide concentration from 400 to 800 p.p.m. led to a 5–35% decrease of these enzyme activities. The largest changes occurred for aldolase, and for transketolase which also catalyses a reversible reaction and is not subject to ‘fine’ regulation.